Development and characterisation of sugar palm [Arenga pinnata (Wurmb) Merr.] fibre reinforced vinyl ester composites - Mohd Roslim, Muhammad Huzaifah (2019)
Recently, environmental issue have raised awareness many parties including researchers and now numerous research are done to replacing synthetic fibres with natural fibres as the main component in composites. Natural fibres are preferred compared to synthetic fibres due to several imminent advantages, such as biodegradable, light in weight, low in cost, and good mechanical properties. With such qualities, sugar palm tree is a plant that has been found to be suitable to be used to produce natural fibres. Hence, this research focused on the capability and the sustainability of sugar palm fibre (SPF) as lignocellulosic reinforcement for polymer composites. For that purposes, this research consist of four parts. In the first part, characterisations of SPFs obtained from three geographical locations i.e. Kuala Jempol (Peninsular Malaysia), Tawau (West Malaysia), and Tasik Malaya (Indonesia) in terms of its mechanical, thermal, physical, morphology, and chemical properties were done. The finding confirmed that, the highest chemical content of cellulose resulted in the highest strength and thermal stability of the fibre. Fibre originating from Kuala Jempol had the highest cellulose content of 44.53%, followed by Indonesia (44.47%) and Tawau (43.75%). Kuala Jempol fibre (233.28 MPa) also had the highest tensile strength, followed by Indonesia (211.03 MPa) and Tawau (201.30 MPa), which was affected by the cellulose content in the fibre. Then, the second part of this research investigated the effect of different fibre content, which are 10 wt.%, 20 wt.%, 30 wt.% and 40 wt.%. From the results, the additions of SPFs to vinyl ester decrease tensile and flexural strength of the composites, which are 25.1 MPa (10 wt.%), 12.5 MPa (20 wt.%), 9.7 MPa (30 wt.%) and 6.1 MPa (40 wt.%) for tensile strength, while for flexural strength, the results recorded 48.5 MPa, 24 MPa, 18.8 MPa and 2.5 MPa for 10 wt.%, 20 wt.%, 30 wt% and 40 wt.%, respectively. However, SPFs improve impact strength of the composites especially at 30 wt% with 5.4 kJ/m². The addition of SPFs also raise the water absorption and thickness swelling of the composites as the presence of fibres in the composites increase water retained in the composites. Besides that, thermal stability of the composites also reduces by the addition of the SPFs that shows the onset temperature of thermal degradation of 10 wt.% was at 270.83˚C, while 40 wt.% was at 196.67˚C. Next, the third part of this research is about the characterisations of SPFs obtained from three geographical locations reinforced vinyl ester composites on the physical, thermal, and mechanical properties. The SPFs were utilized as reinforcement material with a fixed loading of 10 wt.%. The reinforced VE composites were prepared using a wet lay-up compression moulding method. The physical properties examined were water absorption, thickness swelling, and moisture content. To determine the strength of the SPF composites, tests on the tensile, flexural, and impact strength related to mechanical properties were completed. A thermogravimetric analysis (TGA) was completed to observe the thermal properties. This study confirmed that the properties of the composites were affected by the strength of the fibre. The SPF/VE composites obtained from Kuala Jempol had the highest tensile, flexural, and impact strength compared to the SPF/VE composites from Indonesia and Tawau. In addition, SPF Jempol/VE also recorded the highest percentage of water absorption, thickness swelling, and moisture content. A comparison of thermal properties showed that SPF Tawau/VE had highest percentage of mass loss between fibres from the three geographic locations. Finally, the last part of this research is to investigate the effect of soil burial on physical, mechanical and thermal properties of SPF (SPF) reinforced vinyl ester (VE) composites. Neat VE and SPF/VE composites at weight ratio of 10 wt% SPF were prepared using wet hand lay-up method. The specimens were buried in the soil for 0, 200, 400, 600, 800 and 1000 hours to investigate the effect of soil burial to its physical properties (i.e. water absorption), mechanical properties (i.e. tensile, flexural and impact strength) and thermal properties. Obtained results indicated that, the longer soil burial period led to high water absorption of the composites. After 200 hours of soil burial, the SPF/VE composites water uptake increased 0.92% compared to neat VE which is 0.42%. Based on the results, soil burial reduces the mechanical strength of the composites. Tensile, flexural and impact strength decreased rapidly after 200 hours of soil burial compared to neat VE which were 28.24%, 8.04% and 14.83%, respectively. Thermal stability after 200 hours of soil burial increase temperature onset of the SPF composites compared to neat VE. Overall, soil burial increased water absorption, temperature onset of the SPF composites and at the same time decreased the tensile, flexural and impact strength of the composites.